Eksplorasi Perilaku Menyontek Di Kalangan Siswa Sekolah Dasar Di Kota Tasikmalaya - Muhammad Itsnan Shidiq; Syarip Hidayat (Universitas Pendidikan Indonesia Kampus Serang, 2020)
Cheating behavior is a phenomenon that often occurs in the education system in Indonesia. This will have an impact on the loss of moral values inherent in character education. Therefore, character education needs to be implemented early to deal with cheating behavior. The researchers try to describe the results of the exploration of cheating behavior among elementary school students. The approach in this study used a qualitative approach. The method used was descriptive in order to describe the phenomena. The research subjects were students of 4th grade of SDN 1 Cibeuti. Based on the results of students’ interviews, most students had cheated with various reasons. This research observed on 4 dimensions, namely: individualistic-opportunistic, independent-planned, social-active, and social-passive. Based on those four dimensions, the most prominent type is social-passive by 75%. While the individualistic-opportunistic type of 50%. While the social-active type is 25%. While the independent-planned type was not found cheating behavior or equivalent to 0%. So, it can be concluded that students tend to cheat because of difficult subjects. The benefit of this research is that the teacher can find out the main reasons students make and can overcome and reduce the students’ cheating behavior.